Profil Pasien Hemodialisis Inisiasi Di RSUD Arifin Achmad Provinsi Riau Periode Januari – Desember 2017 - Elsa Tubella; Ligat Pribadi Sembiring; Fridayenti Fridayenti (Fakultas Kedokteran Universitas Riau, 2018)
Hemodialysis is defined as the process of separation, filtering, or cleansing of blood through a semipermeable membrane in patients renal failure. Indication of hemodialysis for both diseases is clinical conditions in addition to laboratory results, such as signs of fluid overload, electrolyte imbalance, metabolic acidosis, and signs of anemia. This study purposed to describe the profile of patients initiation hemodialysis in RSUD Arifin Achmad Riau Province Period January-December 2017. This research was a retrospective descriptive. This study used 94 samples. The number of male patients were higher than female patients (60.6%). The most age group was 40-59 years (57.4%). Second degree of hypertension was 46,8%. The study showed 92.55% of patients had anemia, 50% had hyperkalemia, 56.4% had hyponatremia, and 41.5% had acidosis. Patients consisted of 81.9% chronic kidney disease, and 18.1% acute renal failure.